PENGARUH GAYA KEPEMIMPINAN, KOMITMEN ORGANISASI DAN KEPERCAYAAN DIRI TERHADAP KINERJA PEGAWAI KONTRAK KANTOR BAWASLU PROVINSI SULAWESI TENGGARA - Sastriana Djamin; Buyung Sarita; La Ode Bahana Adam (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2022)
This study attempts to: 1.Examine and describe the leadership style , the organization and confidence simultaneously on performance officer at the election supervisory body bawaslu southeast sulawesi; 2.Examine and describe the leadership style on the performance of employees at the election supervisory body bawaslu; southeast Sulawesi. 3.Test organization commitment to performance and said employees at the election supervisory body bawaslu; southeast sulawesi 4.Test and said confidence led to the employee performance at its election supervisory body bawaslu southeast sulawesi .Population research are always 35 people .The whole stock in this research in made as respondents .Instrument parametrik used to answer hypothesis in this research using linear regression multiple through the spss 18.0 version. Research suggests that: , leadership style the commitment and confidence simultaneously can improve the employee performance a contract in election supervisory body bawaslu southeast sulawesi; leadership style have had a positive impact on the employee performance and significant contracts in election supervisory body bawaslu southeast sulawesi; commitment organization have had a positive impact on the employee performance and significant contracts in election supervisory body bawaslu southeast sulawesi; trust have had a positive impact on the employee performance and significant contracts in election supervisory body bawaslu southeast sulawesi